2009
DOI: 10.5694/j.1326-5377.2009.tb02617.x
|View full text |Cite
|
Sign up to set email alerts
|

“HAND ME AN ISOBAR”: a pilot study of an evidence‐based approach to improving shift‐to‐shift clinical handover

Abstract: Objective: To develop, using an evidence‐based approach, a standardised operating protocol (SOP) and minimum dataset (MDS) to improve shift‐to‐shift clinical handover by medical and nursing staff in a hospital setting. Design, setting and participants: A pilot study conducted in six clinical areas (nursing and medical handovers in general medicine, general surgery and emergency medicine) at the Royal Hobart Hospital between 1 October 2005 and 30 September 2008. Data collection and analysis involved triangulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 9 publications
0
40
1
Order By: Relevance
“…This may mean implementing a minimum dataset, such as SBAR (situation–background–assessment–recommendation) while still allowing for customisation to ensure that it meets the needs of the local clinical context. Several of the articles describe the implementation of different standardised tools for improving handover: https://doi.org/10.5694/j.1326-5377.2009.tb02617.x (on shift‐to‐shift clinical handover); 6 https://doi.org/10.5694/j.1326-5377.2009.tb02623.x (on handover from inpatient private mental health care to the community); 7 https://doi.org/10.5694/j.1326-5377.2009.tb02618.x (on improving communication between hospital staff at handover); 8 and https://doi.org/10.5694/j.1326-5377.2009.tb02616.x (on handover from the aged‐care home to the emergency department) 9 …”
Section: The Need For “Flexible Standardisation”mentioning
confidence: 99%
“…This may mean implementing a minimum dataset, such as SBAR (situation–background–assessment–recommendation) while still allowing for customisation to ensure that it meets the needs of the local clinical context. Several of the articles describe the implementation of different standardised tools for improving handover: https://doi.org/10.5694/j.1326-5377.2009.tb02617.x (on shift‐to‐shift clinical handover); 6 https://doi.org/10.5694/j.1326-5377.2009.tb02623.x (on handover from inpatient private mental health care to the community); 7 https://doi.org/10.5694/j.1326-5377.2009.tb02618.x (on improving communication between hospital staff at handover); 8 and https://doi.org/10.5694/j.1326-5377.2009.tb02616.x (on handover from the aged‐care home to the emergency department) 9 …”
Section: The Need For “Flexible Standardisation”mentioning
confidence: 99%
“…The anaesthetist to nurse handover was observed for compliance with elements of the Connect, Observe, Listen, Delegate (COLD) quality improvement tool developed previously by one of the researchers (Botti et al, ; Redley et al ). The Listen step of this process included the elements of Identify, Situation, Observations, Background, Assessment and Recommendation (ISoBAR) (Porteous, Stewart‐Wynne, Connolly, & Crommelin, ; Yee, Wong, & Turner, ) recommended to standardise the verbal communication during PACU handover (Agarwal et al., ; Botti et al, ; Redley et al ).…”
Section: Methodsmentioning
confidence: 99%
“…High patient turnover and a wide range of presentations in the ED create a complex case load, which varies from hour to hour . An effective clinical handover process, whereby information about a patient's care is passed from one healthcare professional to the next accurately and reliably, is essential to ensure continuity of care …”
Section: Introductionmentioning
confidence: 99%
“…Australian research examining medical clinical handover in EDs and in general, has identified that poor handover practices result in incomplete information transfer and consequently repetition of assessments, delayed treatment, medication errors, avoidable readmissions, increased patient morbidity and mortality . Lack of training and poor knowledge of handover processes have been shown to contribute to these errors and inefficiencies …”
Section: Introductionmentioning
confidence: 99%